Water Splitting: Active Site Identification and Evaluation Criteria of In Situ Grown CoTe and NiTe Nanoarrays for Hydrogen Evolution and Oxygen Evolution Reactions (Small Methods 5/2019). Issue 5 (2nd May 2019) - Yang, Liu; Xu, Haoxiang; Liu, Huibing; Cheng, Daojian; Cao, Dapeng
Abstract : In article number1900113 by Daojian Cheng, Dapeng Cao, and co‐workers, in‐situ grown CoTe and NiTe nanoarrays are synthesized as high‐performance bifunctional catalysts for overall water splitting. The active species of the as‐synthesized catalysts for the oxygen evolution reaction (OER) are identified by experiments and theoretical calculations, and a new theoretical evaluation criteria for the hydrogen evolution reaction (HER) is proposed, which can be used as a general criteria to evaluate the HER performance of other electrocatalysts.